PENGADAAN BAHAN PUSTAKA DI PERPUSTAKAAN UNIVERSITAS SARI MUTIARA INDONESIA - Hilda Syaf'aini Harefa (Central Library of Universitas Sebelas Maret, 2017)
The papers aims to determine how the process of procurement of library materials in the library of the University of Sari Mutiara Indonesia. The method used is descriptive qualitative approach. Data was collected through interviews. The results showed as follows: (1) The procurement of library materials in the library-Indonesian USM adapted to the needs of the academic community. (2) System procurement of library materials used by USM library-Indonesia is the purchase, gift or donation and its own publications. (3) System procurement of library materials that are often used by the USM-Indonesian library is oriented to the needs of purchase for USM-Indonesian academicians. Recommendations USM-Indonesian library should make a written procurement policy of library materials as a basis for procurement of library materials in the library USM-Indonesia.